PENGARUH FINANCIAL LITERACY, LIFESTYLE , DAN SOCIAL INFLUENCE TERHADAP MINAT PENGGUNAAN QRIS PADA GENERASI X DI KOTA DENPASAR - Widiantari, Komang Sri; Pramesti, Ni Putu Desya Arimasrani Putri (COMPETITIVE, 2024)
Currently, Financial Technology (Fintech) is developing rapidly and changing people's lifestyles in terms of payments. Payment using QRIS is one form of fintech progress, but in generation x payments using QRIS are still relatively low. This research aims to determine the influence of financial literacy, lifestyle and social influence on interest in using QRIS among generation x in the city of Denpasar. The theory used in this research is the Theory of Planned Behavior (TPB). The population in this study is generation x who uses QRIS, but the exact population numbers are unknown. With a sample size of 65 respondents determined using the hair formula. The data collection technique uses a questionnaire via Google Form. The type of data is quantitative with data analysis using multiple linear regression using the SPSS program. The results of this research are that financial literacy has a significant positive effect on interest in using QRIS, lifestyle has a significant positive effect on interest in using QRIS, social influence has a significant positive effect on interest in using QRIS.